2019
DOI: 10.1097/brs.0000000000003350
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Leadership at Spine Surgery Fellowships

Abstract: Study Design. Cross-sectional study. Objective. To illustrate demographic trends among spine fellowship leaders (FLs). Summary of Background Data. No previous study in the orthopedic literature has analyzed the demographic characteristics or past surgical training of FL in an orthopedic sub-specialty. We attempt to illustrate demographic trends among spine fellowship leadership including fellowship directors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
108
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(112 citation statements)
references
References 17 publications
2
108
1
1
Order By: Relevance
“…One study in the field of general surgery, discussed the relationship between past residents’ rank lists to future academic career path[ 6 ]. Plastic surgery is another subspecialized field that has also evaluated leadership roles and trends in characteristics[ 7 , 8 ]. Previous studies in orthopaedics have considered the pertinent motivating factors impacting the applicant selection process of residency and FDs, as well as the selection process of medical students and residents when considering orthopaedic surgery as a specialty[ 9 - 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…One study in the field of general surgery, discussed the relationship between past residents’ rank lists to future academic career path[ 6 ]. Plastic surgery is another subspecialized field that has also evaluated leadership roles and trends in characteristics[ 7 , 8 ]. Previous studies in orthopaedics have considered the pertinent motivating factors impacting the applicant selection process of residency and FDs, as well as the selection process of medical students and residents when considering orthopaedic surgery as a specialty[ 9 - 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In discussions on appropriate or discrepant representation of gender and cultural diversity, the leadership within orthopaedics has come into focus[ 16 - 19 ]. Two other studies have described demographic characteristics for spine fellowship leaders and adult reconstruction FDs which similarly noted FDs are more likely to have graduated from certain residency and fellowship programs[ 7 , 20 ]. As in this sports medicine cohort, the spine and adult reconstruction cohorts might attract applicants with a predilection to later seek academic leadership roles post-training[ 7 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6,12,13 Recently, a cross-sectional study identifying leadership trends in spine surgery fellowships demonstrated that fellowship directors (FDs) are more likely to have graduated from certain residency and fellowship programs. 4 While these trends have been identified in orthopaedic spine surgery, there is no current literature describing these trends in sports medicine or any other orthopaedic subspecialty.…”
mentioning
confidence: 99%